Biological roles of momilactones: achievements, challenges, and promising approaches to exploit their beneficial properties - Anh, La Hoang; Khanh, Tran Dang; Xuan, Tran Dang (Frontiers in Natural Products, 2023)
Momilactones are defined as every lactone derived from rice husk. To date, these compounds can only be naturally found in rice (Oryza lineage) and moss (Pseudoleskeella papillosa and Hypnum plumaeforme). Their basic structure refers to the (9β-H)-pimarane skeleton bearing a γ-butyrolactone. In this review, the beneficial properties of momilactones, especially momilactones A (MA) and B (MB), including allelopathy, antimicrobials, antioxidants, anti-chronic diseases, anti-inflammation, and anticancer, are highlighted. Additionally, the signaling roles of momilactones in the response of host plants against environmental stresses are discussed, raising the question of whether momilactones act as novel phytohormones that require further comprehensive clarification. In another aspect, we come up with promising approaches to the future exploitation of these valuable compounds based on the current knowledge of their bioactivity mechanisms, biosynthetic pathways, and isolation protocols. However, momilactone biosynthetic processes remain elusive. Moreover, challenges in researching these compounds are mainly due to difficulties in isolation procedures and the lack of commercial sources, which have been least improved over the last half-century. Accordingly, we propose promising strategies to address these present problems and promote the effectiveness of further research, including: i) to improve the efficiency of momilactone extraction and isolation from plant sources; ii) to increase momilactone production applying synthetic models; iii) to generate crops that accumulate greater momilactone contents through genetic engineering approaches; iv) to discover new applications that combine momilactones with other prospective substances for enhancing targeted biological properties and preventing undesirable impacts; and v) to employ smart farming for optimizing the application of momilactones, monitoring their levels, and promoting sustainable agriculture. This paper may provide valuable insights for future strategies, focusing on the exploitation of momilactones for human health-beneficial purposes and the development of green agriculture aligned with sustainable development targets.